A possible human homologue for the mouse mutant disorganisation. Issue 7 (July 1989) - Winter, R M; Donnai, D
Abstract : The mouse mutant disorganisation (Ds) is a semidominant gene with variable penetrance in heterozygotes and lethality in homozygotes; 67% of heterozygotes have multiple defects and the rest have single defects. Fifty-three percent have cranioschisis and execephaly, 40% have hamartomas represented by papillae of variable size and shape protruding from the body, sometimes containing cartilage, and 33% have limb abnormalities. A child is presented with defects similar to those seen in mice heterozygous for Ds. He had shortening of the upper and lower segments of the right leg with a popliteal web and nine toes on the same side. A finger-like structure arose from the abdomen and one kidney was absent. The homology between this infant and Ds mice is discussed and published reports of human cases with similar abnormalities are reviewed.